Anti-GM1 IgG antibodies in Guillain-Barré syndrome: Fine specificity is associated with disease severity - Lardone, Ricardo Dante (2010)
Background: Clinical severity of Guillain-Barré syndrome (GBS) is highly variable, but the immunopathological reason is unknown. Objective: The study was designed to show which antibody parameters are associated with disease severity in GBS patients with serum anti-GM1 IgG antibodies. Methods: Thirty-four GBS patients with anti-GM1 IgG antibodies were grouped into two categories according to disease severity at nadir: mild (grades 1-3 by Hughes functional scale, n=13) and severe (grades 4 and 5, n=21). Titre, affinity, fine specificity and cell binding of anti-GM1 antibodies were obtained and compared between the two groups. Results: No differences in antibody titre (GM1-ELISA) or affinity were found between the two patient groups. In contrast, the severe group showed a significantly higher frequency (95%, vs 46% in the mild group, p=0.002) of specific (not cross-reacting with GD1b) anti-GM1 antibodies. In addition, the severe group also exhibited a higher antibody binding titre to cellular GM1. Conclusions: Differences in fine specificity of antibodies are strong indications that different regions of the GM 1-oligosaccharide are involved in antibody binding. High titres of specific anti-GM1 antibody binding to cellular GM1 can be explained by antigen exposure, that is, GM1 exposes or forms mainly epitopes recognised by specific antibodies, and 'hides' those involved in binding of crossreacting antibodies. Thus, the fine specificity of anti-GM 1 antibodies may influence disease severity by affecting antibody binding to cellular targets. Additionally, since antibody specificity studies are relatively easy to implement, fine specificity could be considered a useful predictor of disease severity.